(untitled) - Kezar, Adrianna J. (San Francisco, 2005)
As public policy and institutional decisions in the US focus higher education increasingly on revenue generation and the benefits for individual students, it has shifted away from its historic commitment to serving the public good through activities such as research, leadership training, the critique of public policy, and the increase of economic development. The volume's academic contributors look at why the social charter between higher education and the public is being altered, lost, or even rejected; why this matters; and how college and university administrators can examine and build the role their institutions play in the larger public good.
Keywords: Education, higher,Education, higher; Social aspects,Aims and objectives; United States,United States